2007
DOI: 10.1016/j.juro.2006.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Full Publication of Studies Presented in Abstract Form at the Annual Meeting of the American Urological Association

Abstract: Nonpublication of research findings is a problematic issue that affects more than half of studies 2 years after presentation at the American Urological Association national meeting. Abstracts from the United States and those providing statistical testing were more likely to be published in full text form. Further efforts are warranted to identify and eliminate factors that hinder publication of research to bring it to the scrutiny of a broad audience of urologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 16 publications
6
44
1
3
Order By: Relevance
“…This rate is comparable with that of other medical The outcome of abstracts presented at the USCAP J Song et al societies with published reports, which typically range from 30 to 50%. [1][2][3][4][5][6] The variation in reported rates may be partly due to different follow-up times, because some studies included publications as far as 5 years after abstract presentation. In a large-scale study, von Elm et al 1 analyzed 19 123 abstracts presented in 234 biomedical meetings from 1957 to 1998, and found the overall publication rates after 1, 2, 3, 4, and 6 years to be 12, 27, 37, 41, and 44% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rate is comparable with that of other medical The outcome of abstracts presented at the USCAP J Song et al societies with published reports, which typically range from 30 to 50%. [1][2][3][4][5][6] The variation in reported rates may be partly due to different follow-up times, because some studies included publications as far as 5 years after abstract presentation. In a large-scale study, von Elm et al 1 analyzed 19 123 abstracts presented in 234 biomedical meetings from 1957 to 1998, and found the overall publication rates after 1, 2, 3, 4, and 6 years to be 12, 27, 37, 41, and 44% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to some other studies that showed a more favorable outcome of abstracts with US origin. 1,6 Pathology studies involving diagnostic and prognostic markers frequently require statistical analysis. Our data showed that abstracts explicitly mentioning statistical methods had approximately the same publication rate as did those that did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The publication rate for the first ICNU was lower than those for international relevant congresses held by the American urological association (AUA, 37.8% -55.0%) (6,8,10), European association of urology (EAU, 47.3%) (11), British association of urological surgeons (BAUS, 31.6%) (11), and ICS Meeting (61.6%) (12). Also, the publication rate of the abstracts of three annual nephrology meetings (American society of nephrology (ASN), National kidney foundation (NKF), and European renal association (ERA)) was 42% (13), which was higher than the rate found in our study.…”
Section: Discussionmentioning
confidence: 81%
“…Similar publication rates ranging from 30% to 50% have been observed in other clinical disciplines, including anesthesiology, pediatrics, otolaryngology, and urology. [6][7][8][9] In this context, we are encouraged by our observation that at least 56% of abstracts for projects supported by the Anatomic Pathology Research Fund have led to publication. It is tempting to speculate based on our early experience with this funding mechanism that the relatively higher publication rate of our abstracts is related to improvements in the scientific design, merit, and rigor of the funded projects afforded by the evaluation process.…”
Section: Commentmentioning
confidence: 99%